2010
DOI: 10.1038/pj.2010.82
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of hyperbranched polycarbonate by novel polymerization of di-tert-butyl tricarbonate with 1,1,1-tris(4-hydroxyphenyl)ethane

Abstract: Hyperbranched polycarbonates (HBPCs) with M n ¼2.1-7.1Â10 3 were synthesized by A 2 +B 3 polymerization using di-tert-butyl tricarbonate as the A 2 monomer and 1,1,1-tris(4-hydroxyphenyl)ethane as the B 3 monomer. A 2 +B 3 polymerization with different feed ratios was achieved, controlling the degree of branching (DB) and the ratio of terminal functional groups. The DB of the HBPCs is 0.5-0.7. The Boc-terminated PC was prepared by either a 1-pot or a 2-pot synthesis. In contrast, PC with terminal phenol groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…For hyperbranched polyimides from 2,2-bis(3,4-dicarboxylphenyl) hexafluoropropane dianhydride (A 2 ) and 2,4,6-triaminopyrimidine (B 3 ), 139 the DB increased from 0.36 to 0.83 when the feed ratio of A 2 : B 3 was increased from 1 : 1 to 2 : 1. Nishikubo et al 145 observed the same phenomenon in the polycondensation reaction of di-tertbutyl tricarbonate (A 2 ) and 1,1,1-tris(4-hydroxyphenyl)ethane (B 3 ), where the DB of the hyperbranched polycarbonates increased from 0.52 to 0.78 when the feed ratio was increased from 1 : 1 to 2 : 1. Similarly, for typical hyperbranched poly (amine-ester)s from the polycondensation between diesters (A 2 ) and triethanolamine (B 3 ), catalyzed by Candida antarctica lipase B, 146 the DB of poly(amine-ester)s at a feed ratio of 2 : 1 was much higher than that at a feed ratio of 1 : 1.…”
Section: Controlling Strategies For the Topological Structurementioning
confidence: 67%
“…For hyperbranched polyimides from 2,2-bis(3,4-dicarboxylphenyl) hexafluoropropane dianhydride (A 2 ) and 2,4,6-triaminopyrimidine (B 3 ), 139 the DB increased from 0.36 to 0.83 when the feed ratio of A 2 : B 3 was increased from 1 : 1 to 2 : 1. Nishikubo et al 145 observed the same phenomenon in the polycondensation reaction of di-tertbutyl tricarbonate (A 2 ) and 1,1,1-tris(4-hydroxyphenyl)ethane (B 3 ), where the DB of the hyperbranched polycarbonates increased from 0.52 to 0.78 when the feed ratio was increased from 1 : 1 to 2 : 1. Similarly, for typical hyperbranched poly (amine-ester)s from the polycondensation between diesters (A 2 ) and triethanolamine (B 3 ), catalyzed by Candida antarctica lipase B, 146 the DB of poly(amine-ester)s at a feed ratio of 2 : 1 was much higher than that at a feed ratio of 1 : 1.…”
Section: Controlling Strategies For the Topological Structurementioning
confidence: 67%
“…Hyperbranched polycarbonates (HBPC) have been known since the early works of Bolton and Wooley , concerning synthesis and properties of aromatic analogues of linear, commercially available bisphenol A-based polycarbonates, but there is still a limited number of such polymers reported in the literature. Recently, similar aromatic HBP’s were reported by Nishikubo et al, who synthesized HBPC according to double monomer methodology (DMM) using di- tert -butyl tricarbonate and 1,1,1-tris(4-hydroxyphenyl)ethane as A 2 and B 3 monomers . Synthesis and functionalization with methacrylic acid residues of aromatic hyperbranched polycarbonates based on bisphenol A bis(chloroformate) and 1,1,1-tris(4-hydroxyphenyl)ethane performed in the presence of pyridine in THF were reported by the same authors .…”
Section: Introductionmentioning
confidence: 69%
“…Recently, similar aromatic HBP's were reported by Nishikubo et al, who synthesized HBPC according to double monomer methodology (DMM) using di-tert-butyl tricarbonate and 1,1,1-tris(4-hydroxyphenyl)ethane as A 2 and B 3 monomers. 14 Synthesis and functionalization with methacrylic acid residues of aromatic hyperbranched polycarbonates based on bisphenol A bis(chloroformate) and 1,1,1-tris(4hydroxyphenyl)ethane performed in the presence of pyridine in THF were reported by the same authors. 15 Aliphatic starshaped polycarbonates were reported by Hult and coworkers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Nowadays, these aromatic alcohols are used for countless applications, e.g. epoxy resins [34][35][36] , phenolic resins (resorcinol) [37][38][39][40] , polyesters [41][42][43][44][45][46] , dyes (fluorescin, eosin) 47,48 , medical diagnostics 49 and other usages 50 , which make them promising candidates for the use of recyclable and reprocessable polymer networks. Moreover, we introduce 2,7-naphtalendiol and 1,1,1-tris(4-hydroxyphenyl)ethane as less toxic alternatives to the widely established toxic and carcinogenic bisphenol-A and resorcin-based polymers, which are increasingly being avoided and replaced by industry.…”
Section: Introductionmentioning
confidence: 99%